The novel MKL target gene myoferlin modulates expansion and senescence of hepatocellular carcinoma - Hermanns, Constanze; Holzer, Kerstin; Waldburger, Nina; Rössler, Stephanie; Singer, Stephan (Oncogene, 2017)
Megakaryoblastic Leukemia 1 and 2 (MKL1/2) are transcriptional coactivators of Serum Response Factor (SRF) with an essential role for hepatocellular carcinoma (HCC) growth and oncogene-induced senescence. In this report, we identified myoferlin as a novel MKL/SRF target gene by gene expression profiling and verification in vivo in HCC xenografts. Myoferlin was overexpressed in human and murine HCCs triggered by conditional expression of constitutively active SRF-VP16 protein in hepatocytes. Furthermore, myoferlin was required for HCC cell invasion, proliferation and anchorage-independent cell growth. We provide evidence that myoferlin is a crucial gene target of MKL1/2 mediating its effect on oncogene-induced senescence by modulating the activation state of the EGFR and downstream MAPK and p16-/Rb pathways. Depletion of myoferlin in tumour cells from SRF-VP16-derived murine HCCs induced a senescence phenotype. These findings identify MKL1/2 and myoferlin as novel therapeutic targets to treat human HCC by a senescence-inducing strategy.